Design methodologies to determine optimal staging of membrane-aerated biofilm reactors for mainstream treatment with anammox. (7th October 2022) - Wagner, Brett M.; Daigger, Glen T.; Love, Nancy. G.
Abstract: Partial nitritation anammox (PNA) membrane-aerated biofilm reactors (MABRs) can be used in mainstream nitrogen removal to help facilities reduce their energy consumption. Previous PNA MABR research has not investigated the impacts of staging, i.e. arraying MABRs in series, on their nitrogen removal performance, operation, and ability to suppress nitrite oxidizing bacteria. In this paper, a mathematical model simulated PNA MABR performance at different influent total ammonia concentrations and loadings. A design methodology for staging PNA MABRs was created and found that the amount of membrane surface area is dependent upon the total ammonia-nitrogen concentration and loading, and the air loading to the membrane must be proportional to the total ammonia-nitrogen loading to maximize the total inorganic nitrogen (TIN) removal rate. This led to approximately equal-sized stages that each had a TIN removal percentage of 71% of the influent total ammonia nitrogen. Staging a treatment train resulted in 9.8% larger total ammonia and 9.3% larger total nitrogen removal rates when compared with an un-staged reactor. The un-staged reactor also was not able to produce an effluent total ammonia concentration below 5 mg N/L which would be necessary for many facilities' permits. HIGHLIGHTS: Staging PNA MABRs requires a methodology that suppresses NOB and prevents O2 inhibition of AMX . The size of each stage depends on the NHx -N loading, NHx -N concentration, and the membrane air loading to the reactor. This method will typically result in equal-sized stages. Staging a treatment train increases the NHx -N removal rate by 10% and the total nitrogen removal rate by 9% when compared with an un-staged reactor. Graphical Abstract